Management of road tunnels: Construction, maintenance and lighting costs. (January 2016) - Moretti, Laura; Cantisani, Giuseppe; Di Mascio, Paola
Highlights: LCCA to compare construction, maintenance, and lighting costs needed to manage a highway tunnel. LED lighting system to maximize energy saving and road safety. Construction, maintenance road pavement costs and lighting costs during the service life of tunnel. Lighting costs related to concrete and asphalt tunnel pavement. Abstract: This paper presents a life cycle cost analysis, which compares construction, maintenance, and lighting costs needed to manage a highway tunnel. As regards the decision making process, it often considers only construction costs. Instead even maintenance and lighting, especially related to road tunnels, cause important cash flows. Therefore, both construction and managing costs have to be planned, in order to assess the cheapest solution. The lighting system of a road tunnel must guarantee the visual guidance for users moving at design speed and without hazardous actions. In this case study, the authors designed the pavement according to Italian standards and the lighting system according to Italian and European technical rules (UNI and UNI EN standards). They used LED technologies to maximize energy saving and road safety. The examined case study shows the importance of the surface pavement material, since it may contribute to the inter-reflected light and reduce electric energy consumption.